システマティックレビューおよび医薬品副作用データベース解析に基づく解熱鎮痛薬アセトアミノフェンの動脈管におよぼす薬理作用に関する探索的検討 - 門脇, 大介; 難波, 七海; 石塚, 洋一; 近藤, 悠希 (日本薬理学会年会要旨集, 2022)
Background: Acetaminophen (APAP) is widely used as an antipyretic analgesic with a higher safety profile than non-steroidal anti-inflammatory drugs (NSAIDs), however its pharmacological mechanisms are still fully unclear. In this study, we conducted a meta-analysis and database analysis focusing on the effect of APAP on the "ductus arteriosus," i.e., the effect on treatment of patent ductus arteriosus (PDA) in low birthweight infants and the occurrence of adverse reactions of fetal ductus arteriosus occlusion when administered to pregnant women. Methods: Articles on the efficacy of treatment for PDA were collected, and a meta-analysis was performed. The database analysis was conducted by collecting records about the fetal ductus arteriosus contraction from the "JADER" database. Results and Discussion: The combined results of the randomized controlled trials suggest that APAP has some therapeutic effect on PDA. The results of meta-analysis should be interpreted with caution, given the insufficient number and quality of studies analyzed. In addition, an analysis using JADER detected an adverse event signal of fetal ductal arteriosus occlusion was detected. At present, these findings do not support the APAP therapy for the disease, nor rule out the use of APAP in pregnant women. However, these data suggest that APAP shows the effects on ductus arteriosus.